Myoglobin Concentration and Oxygen Stores in Different Functional Muscle Groups from Three Small Cetacean Species - Marina Arregui; Emily M. Singleton; Pedro Saavedra; D. Ann Pabst; Michael J. Moore; Eva Sierra; Miguel A. Rivero; Nakita Câmara; Misty Niemeyer; Andreas Fahlman; William A. McLellan; Yara Bernaldo de Quirós (Animals, 2021)
Compared with terrestrial mammals, marine mammals possess increased muscle myoglobin concentrations (Mb concentration, g Mb · 100g−1 muscle), enhancing their onboard oxygen (O2) stores and their aerobic dive limit. Although myoglobin is not homogeneously distributed, cetacean muscle O2 stores have been often determined by measuring Mb concentration from a single muscle sample (longissimus dorsi) and multiplying that value by the animal’s locomotor muscle or total muscle mass. This study serves to determine the accuracy of previous cetacean muscle O2 stores calculations. For that, body muscles from three delphinid species: Delphinus delphis, Stenella coeruleoalba, and Stenella frontalis, were dissected and weighed. Mb concentration was calculated from six muscles/muscle groups (epaxial, hypaxial and rectus abdominis; mastohumeralis; sternohyoideus; and dorsal scalenus), each representative of different functional groups (locomotion powering swimming, pectoral fin movement, feeding and respiration, respectively). Results demonstrated that the Mb concentration was heterogeneously distributed, being significantly higher in locomotor muscles. Locomotor muscles were the major contributors to total muscle O2 stores (mean 92.8%) due to their high Mb concentration and large muscle masses. Compared to this method, previous studies assuming homogenous Mb concentration distribution likely underestimated total muscle O2 stores by 10% when only considering locomotor muscles and overestimated them by 13% when total muscle mass was considered.